Maintenance of dental records and awareness of forensic odontology among pakistani dentists: a mixed-method study with implications for dental data repository - Haifa Saquib Baqai; Syed Jaffar Abbas Zaidi; Qaiser Ali Baig; Muhammad Bilal Bashir; Madiha Anwar; Asma Saher Ansari (BMC, 2023)
Abstract Objective Dental records and forensic odontology play an important role in both healthcare and the legal system, aiding in personalized patient care, human identification, and legal proceedings. This study aims to investigate dental record-keeping practices and assess the awareness of forensic odontology among Pakistani dentists over 12 months. This study aims to collect data from 500 dentists, identify areas for enhancement, and develop a strategic action plan to improve record-keeping quality and forensic odontology application, culminating in a comprehensive dental data repository to support legal and criminal investigations in Pakistan. Methodology This study employed a mixed-method approach conducted at Hamdard Dental College from January to March 2023. The quantitative phase involved distributing questionnaires to 463 dentists, chosen through stratified random sampling. Out of these, 413 responded, yielding an 86% response rate. These questionnaires focused on dental record-keeping practices and dentists' awareness of forensic odontology. Subsequently, based on the questionnaire results, face-to-face interviews were conducted with 20 purposively selected dentists to gain deeper insight into the challenges and potential solutions. Data from both phases were integrated and analyzed accordingly. Results The study included 413 participants, mainly females (79%), with ages ranging from 27 to 65 years and an average age of 46.4 years. Most dentists had 5-20 years of work experience (53%), and most (87.4%) were practicing in private clinical settings. All the dentists generated medical and dental records, but the duration of their record-keeping varied, with some maintaining them for up to a year and others for two years or longer. Five themes were generated from the qualitative content analysis. These themes were dentists' perceptions, barriers and challenges, knowledge and awareness, and improvement strategies. Conclusion Our study revealed that local practitioners in Pakistan exhibit subpar practices in dental record-keeping and maintenance of patient history, irrespective of whether they use a digital or traditional file-based system. Even though dentists are cognizant of the importance of record-keeping, they do not actively maintain comprehensive records. This suggests the need for improved training and system improvements to address the gaps in record-keeping practices.